EFEKTIFITAS PENGAJARAN DARING MENGGUNAKAN MEDIA DIGITAL TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SEKOLAH DASAR - Fauziah, Muhardila; Hartati, Tatat; Damaianti, Vismaia S; Sholehuddin, Muhammad (PD PGMI se Indonesia, 2021)
The impact of COVID19 has crippled not only the economic field but also the field of education. Indonesia is one of the countries affected by COVID19 since March 2020. The education process must continue as the government changes the learning activities conducted face-to-face now conducted online. Online learning makes education workers have to be creative and innovative in delivering lessons, especially in grade 1 students. Early reading skills in students are an important concern for teachers and parents who the author chooses to use digital media (YouTube) in the online learning process. The purpose of this research is to find out the influence of digital media (YouTube) on students' early reading ability; to find out the difference in students' initial reading ability using digital media (YouTube) with students without digital media (YouTube). This research uses quantitative methods with quasi-experimental approach. The results of this study showed that the normality test of Shapiro wilk value > 0.05 which means normal distribution. Next Test Paired simple T test with pretest value and posttest experimental group obtained Sig score. (2-tailed) of 0.000 < 0.05 and for control classes of 0.002 < 0.05 in conclusion there is an average difference in students' initial reading ability; and independent sample T test results obtained by Sig (2-tailed) data of 0.045 < 0.05 this score shows that there is a significant difference in students' initial reading ability by using digital media (YouTube) with students without using digital media (YouTube). Based on the results obtained online learning using digital media (YouTube) is very effective to improve the ability to read the beginnings of grade 1 elementary school students.